1997
DOI: 10.1161/01.str.28.12.2483
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement for 10% Categories of Angiographic Carotid Stenosis

Abstract: Background and Purpose Although the reliability of the assessment of severe 70% to 99% carotid stenosis by carotid angiography has been proven excellent, this may not necessarily be the case for a more detailed classification of carotid stenoses by 10% categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our results are similar to those obtained in two previous studies of the interobserver variability of measurement of stenosis from DSA, which found κ values indicating moderate to good agreement. 11 12 We did not measure intraobserver variability, for the reasons given in Results, but it is likely to be no worse than the interobserver variability.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those obtained in two previous studies of the interobserver variability of measurement of stenosis from DSA, which found κ values indicating moderate to good agreement. 11 12 We did not measure intraobserver variability, for the reasons given in Results, but it is likely to be no worse than the interobserver variability.…”
Section: Discussionmentioning
confidence: 99%